Розробка апаратно-програмної тестової платформи для БСМ - Винокуров, О. О. (ХНУРЕ, 2019)
To provide communication with a hardware and software test platform, there is a solution by organizing a radio network based on the ZigBee communication protocol. That will allow to combine test nodes into one network to control and monitor the operation of the tested modules with low power consumption with large network sizes. This network allows you to quickly find the fault, and the topology of the self-contained network will redistribute the data paths. Such networks are used to automate housing, medical equipment and industrial monitoring and control.
Keywords: беспроводная сенсорная сеть; ZigBee